Independent study (an overview) / Jelani Sulaiman - Sulaiman, Jelani (Universiti Teknologi MARA Cawangan Pahang, 1996)
According to Gagne and Driscoll (1988. p. 133). "a high priority goal often cited 'for education is to teach students to be self-learners and independent thinkers". In this respect. independent study has a vital role to play in promoting quality learning and at ensuring that the school experiences of every learner become more fulfilling, Independent studies are structured to meet the needs of able and advanced students to undertake more sophisticated and in depth investigations in their specific fields of interest which would not be possible in a traditional classroom set-up. An independent study, in order to be successful, requires a high degree of cooperation and understanding between both the student and the faculty advisor. This paper provides an overview on the topic of independent study, looking specifically at the aims of independent study. the problems relating to independent study, and the ways to ensure the success of independent study.